EVALUATION OF THE SWARM MVMO FOR PHOTOVOLTAIC PARAMETER ESTIMATION IN A DOUBLE-DIODE MODEL - de Paula Santos, Gustavo Henrique; Tanca Villanueva, Moisés Carlos; Tito Cari, Elmer Pablo (Revista Brasileira de Energia Solar, 2024)
Photovoltaic energy is expanding due to its generation performance, cost, and useful life. In this regard, developing models and techniques to enhance system efficiency is essential. Analytical, metaheuristic, and hybrid methods have been used to estimate the parameters of Single-Diode Model (SDM) and Double-Diode Model (DDM), but none solve all the problems, thus requiring the development of new techniques. In this work, the Swarm MVMO method was used to estimate the parameters of the double diode model using data from the photovoltaic cell RTC France. The results obtained show that Swarm MVMO was effective, reaching the same level of RMSE as other algorithms in the literature and achieving a good fit in the I-V and P-V curves.